Difference between revisions of "009B Sample Midterm 2, Problem 4"

From Math Wiki
Jump to navigation Jump to search
Line 7: Line 7:
 
!Foundations:    
 
!Foundations:    
 
|-
 
|-
|'''1.''' Integration by parts tells us <math style="vertical-align: -15px">\int u~dv=uv-\int v~du.</math>
+
|'''1.''' Integration by parts tells us  
 
|-
 
|-
|'''2.''' How would you integrate <math style="vertical-align: -15px">\int e^x\sin x~dx?</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -15px">\int u~dv=uv-\int v~du.</math>
 +
|-
 +
|'''2.''' How would you integrate &nbsp;<math style="vertical-align: -15px">\int e^x\sin x~dx?</math>
 
|-
 
|-
 
|
 
|
::You could use integration by parts.
+
&nbsp; &nbsp; &nbsp; &nbsp; You can use integration by parts.
 
|-
 
|-
 
|
 
|
::Let <math style="vertical-align: -5px">u=\sin(x)</math> and <math style="vertical-align: 0px">dv=e^x~dx.</math> Then, <math style="vertical-align: -5px">du=\cos(x)~dx</math> and <math style="vertical-align: 0px">v=e^x.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; Let &nbsp;<math style="vertical-align: -5px">u=\sin(x)</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">dv=e^x~dx.</math>  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Then, &nbsp;<math style="vertical-align: -5px">du=\cos(x)~dx</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">v=e^x.</math>
 
|-
 
|-
 
|
 
|
::Thus, <math style="vertical-align: -15px">\int e^x\sin x~dx\,=\,e^x\sin(x)-\int e^x\cos(x)~dx.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; Thus, &nbsp;<math style="vertical-align: -15px">\int e^x\sin x~dx=e^x\sin(x)-\int e^x\cos(x)~dx.</math>
 
|-
 
|-
 
|
 
|
::Now, we need to use integration by parts a second time.
+
&nbsp; &nbsp; &nbsp; &nbsp; Now, we need to use integration by parts a second time.
 
|-
 
|-
 
|
 
|
::Let <math style="vertical-align: -5px">u=\cos(x)</math> and <math style="vertical-align: 0px">dv=e^x~dx.</math> Then, <math style="vertical-align: -5px">du=-\sin(x)~dx</math> and <math style="vertical-align: 0px">v=e^x.</math> So,
+
&nbsp; &nbsp; &nbsp; &nbsp; Let &nbsp;<math style="vertical-align: -5px">u=\cos(x)</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">dv=e^x~dx.</math>  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Then, &nbsp;<math style="vertical-align: -5px">du=-\sin(x)~dx</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">v=e^x.</math>
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Therefore,
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int e^x\sin x~dx} & = & \displaystyle{e^x\sin(x)-(e^x\cos(x)-\int -e^x\sin(x)~dx}\\
 
\displaystyle{\int e^x\sin x~dx} & = & \displaystyle{e^x\sin(x)-(e^x\cos(x)-\int -e^x\sin(x)~dx}\\
 
&&\\
 
&&\\
Line 34: Line 42:
 
|-
 
|-
 
|
 
|
::Notice, we are back where we started.  
+
&nbsp; &nbsp; &nbsp; &nbsp; Notice, we are back where we started.  
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp; Therefore, adding the last term on the right hand side to the opposite side, we get
::So, adding the last term on the right hand side to the opposite side, we get
 
 
|-
 
|-
 
|
 
|
::<math style="vertical-align: -13px">2\int e^x\sin (x)~dx\,=\,e^x(\sin(x)-\cos(x)).</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -13px">2\int e^x\sin (x)~dx=e^x(\sin(x)-\cos(x)).</math>
 
|-
 
|-
 
|
 
|
::Hence, <math style="vertical-align: -15px">\int e^x\sin (x)~dx\,=\,\frac{e^x}{2}(\sin(x)-\cos(x))+C.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; Hence, &nbsp;<math style="vertical-align: -15px">\int e^x\sin (x)~dx=\frac{e^x}{2}(\sin(x)-\cos(x))+C.</math>
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 50: Line 58:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We proceed using integration by parts. Let <math style="vertical-align: -5px">u=\sin(2x)</math> and <math style="vertical-align: 0px">dv=e^{-2x}dx.</math> Then, <math style="vertical-align: -5px">du=2\cos(2x)dx</math> and <math style="vertical-align: -13px">v=\frac{e^{-2x}}{-2}.</math>
+
|We proceed using integration by parts.  
 +
|-
 +
|Let &nbsp;<math style="vertical-align: -5px">u=\sin(2x)</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">dv=e^{-2x}dx.</math>  
 +
|-
 +
|Then, &nbsp;<math style="vertical-align: -5px">du=2\cos(2x)dx</math>&nbsp; and &nbsp;<math style="vertical-align: -13px">v=\frac{e^{-2x}}{-2}.</math>
 
|-
 
|-
|So, we get  
+
|Thus, we get  
 
|-
 
|-
|  
+
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int e^{-2x}\sin (2x)~dx} & = & \displaystyle{\frac{\sin(2x)e^{-2x}}{-2}-\int \frac{e^{-2x}2\cos(2x)~dx}{-2}}\\
 
\displaystyle{\int e^{-2x}\sin (2x)~dx} & = & \displaystyle{\frac{\sin(2x)e^{-2x}}{-2}-\int \frac{e^{-2x}2\cos(2x)~dx}{-2}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\sin(2x)e^{-2x}}{-2}+\int e^{-2x}\cos(2x)~dx.}\\
+
& = & \displaystyle{\frac{\sin(2x)e^{-2x}}{-2}+\int e^{-2x}\cos(2x)~dx.}
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
Line 65: Line 77:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we need to use integration by parts again. Let <math style="vertical-align: -5px">u=\cos(2x)</math> and <math style="vertical-align: 0px">dv=e^{-2x}dx.</math> Then, <math style="vertical-align: -5px">du=-2\sin(2x)dx</math> and <math style="vertical-align: -13px">v=\frac{e^{-2x}}{-2}.</math>
+
|Now, we need to use integration by parts again.  
 +
|-
 +
|Let &nbsp;<math style="vertical-align: -5px">u=\cos(2x)</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">dv=e^{-2x}dx.</math>  
 +
|-
 +
|Then, &nbsp;<math style="vertical-align: -5px">du=-2\sin(2x)dx</math>&nbsp; and &nbsp;<math style="vertical-align: -13px">v=\frac{e^{-2x}}{-2}.</math>
 
|-
 
|-
|So, we get  
+
|Therefore, we get  
 
|-
 
|-
 
|
 
|
::<math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}+\frac{\cos(2x)e^{-2x}}{-2}-\int e^{-2x}\sin(2x)~dx</math>.
+
&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}+\frac{\cos(2x)e^{-2x}}{-2}-\int e^{-2x}\sin(2x)~dx.</math>
 
|}
 
|}
  
Line 76: Line 92:
 
!Step 3: &nbsp;
 
!Step 3: &nbsp;
 
|-
 
|-
|Notice that the integral on the right of the last equation in Step 2 is the same integral that we had at the beginning of the problem.  
+
|Notice that the integral on the right of the last equation in Step 2
 +
|-
 +
|is the same integral that we had at the beginning of the problem.  
 
|-
 
|-
|So, if we add the integral on the right to the other side of the equation, we get
+
|Thus, if we add the integral on the right to the other side of the equation, we get
 
|-
 
|-
|
+
| &nbsp; &nbsp; &nbsp; &nbsp; <math>2\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}+\frac{\cos(2x)e^{-2x}}{-2}.</math>
::<math>2\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}+\frac{\cos(2x)e^{-2x}}{-2}.</math>
 
 
|-
 
|-
 
|Now, we divide both sides by 2 to get  
 
|Now, we divide both sides by 2 to get  
 
|-
 
|-
|
+
| &nbsp; &nbsp; &nbsp; &nbsp; <math>\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-4}+\frac{\cos(2x)e^{-2x}}{-4}.</math>
::<math>\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-4}+\frac{\cos(2x)e^{-2x}}{-4}.</math>
 
 
|-
 
|-
 
|Thus, the final answer is  
 
|Thus, the final answer is  
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{e^{-2x}}{-4}((\sin(2x)+\cos(2x))+C.</math>
::<math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{e^{-2x}}{-4}((\sin(2x)+\cos(2x))+C.</math>
 
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
| &nbsp;&nbsp; <math>\frac{e^{-2x}}{-4}((\sin(2x)+\cos(2x))+C</math>
+
| &nbsp;&nbsp; &nbsp; &nbsp; <math>\frac{e^{-2x}}{-4}((\sin(2x)+\cos(2x))+C</math>
 
|}
 
|}
 
[[009B_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]

Revision as of 11:16, 9 April 2017

Evaluate the integral:


Foundations:  
1. Integration by parts tells us
       
2. How would you integrate  

        You can use integration by parts.

        Let    and  

        Then,    and  

        Thus,  

        Now, we need to use integration by parts a second time.

        Let    and  

        Then,    and  
        Therefore,

       

        Notice, we are back where we started.

        Therefore, adding the last term on the right hand side to the opposite side, we get

       

        Hence,  


Solution:

Step 1:  
We proceed using integration by parts.
Let    and  
Then,    and  
Thus, we get

       

Step 2:  
Now, we need to use integration by parts again.
Let    and  
Then,    and  
Therefore, we get

       

Step 3:  
Notice that the integral on the right of the last equation in Step 2
is the same integral that we had at the beginning of the problem.
Thus, if we add the integral on the right to the other side of the equation, we get
       
Now, we divide both sides by 2 to get
       
Thus, the final answer is
       


Final Answer:  
      

Return to Sample Exam